Comparing Blood Loss Estimates by Medical Laypeople in Online and In-person Formats using SABLE. (September 2021) - Phillips, Rachel; Friberg, Marc; Cronqvist, Mattias Lantz; Prytz, Erik
To design interventions for teaching laypeople how to respond in hemorrhage situations, it is necessary to understand factors that influence their perception of blood loss. Although lab-based research offers more experimental control, it limits access to certain kinds of participants. Therefore, the purpose of this study was to compare results from an online administration of a web-based application (SABLE) to data collected using the same application in a lab. Participants viewed 78 5-second video clips of simulated bleeding injuries with a male or female victim and different volumes of blood loss. They estimated the volume of blood loss after each video. The results replicated the general findings from prior research and revealed no significant differences in estimations or estimation accuracy between the online and lab-based administration of SABLE. Results are discussed in terms of applicability to research practice.